TEACHING LISTENING COMPREHENSION THROUGH PODCASTS AND AUDIOBOOKS - Rasulova S.U,; Temirova Hulkar. N, (TADQIQOTLAR, 2025)
Abstract:  Listening  comprehension  plays  a  crucial  role  in  the  process  of language acquisition, yet it remains one of the most challenging skills for learners to master. Traditional classroom methods often rely on scripted dialogues or repetitive drills  that  fail  to  reflect  real-life  communication.  With  the  rise  of  digital  media, podcasts  and  audiobooks  have  emerged  as  effective  tools  to  enhance  listening comprehension through authentic, engaging, and context-rich audio content. This article explores how podcasts and audiobooks can be used in language classrooms to improve students’ listening skills. It examines theoretical perspectives, pedagogical approaches, and classroom practices supported by empirical evidence. The findings demonstrate that integrating podcasts and audiobooks into instruction enhances  learners’  exposure  to  authentic  language,  improves  pronunciation  and vocabulary retention, and fosters independent and lifelong learning.